METEOROLOGICAL VARIABLES AND SENSORIAL QUALITY OF COFFEE IN THE MANTIQUEIRA REGION OF MINAS GERAIS - Borém, Flávio Meira; Luz, Marcos Paulo Santos; Sáfadi, Thelma; Volpato, Margarete Marin Lordelo; Alves, Helena Maria Ramos; Borém, Rosângela Alves Tristão; Maciel, Daniel Andrade (Coffee Science - ISSN 1984-3909, 2019)
The objective of this study was to identify meteorological variables related to the sensorial quality of the coffees from Mantiqueira region in Minas Gerais. Meteorological conditions are strongly related to the coffee’s sensorial characteristics, however, there aren’t many studies quantifying this relation. Air temperature and rainfall data were collected and spatialized for regional analysis. These were associated to the 2007 through 2011 coffees’ beverage scores. The region is stratified according to relief characteristics. The bigger frequency of high scores occurred on the region’s central-south, where coffee cultivation is performed above 900 m altitude. For the in loco study, meteorological data and coffee samples were collected in selected pilot areas. Coffee crops were selected in three altitude ranges: below 1000 m, between 1000 and 1200 m, and over 1200 m. Above 1000 m the meteorological variable that presented the biggest variation was the air temperature. Above 1000 m the smallest thermal amplitude occurred, which provided superior quality coffees. The study demonstrates the importance of the meteorological variable characterization aiming to identify locations with greater vocation to the specialty coffees production.